A Review of Air Conditioning Load Aggregation in Distribution Networks - Wang, He; Chen, Hongfeng; Li, Yan; Liu, Sumei (Frontiers in Energy Research, 2022)
In the context of global energy transformation, it is particularly important to tap the potential of flexible load on the distribution network side to participate in grid operation. As an important flexible adjustable load in the distribution network, air conditioning loads have typical characteristics of thermal energy storage, rapid response, and flexible scheduling, which is an ideal load resource. Effective and reliable load aggregation technology of air conditioning load participates is the premise of operation in a power grid. In order to better understand the current research level of air conditioning load aggregation technology and make full use of the existing research results to carry out further research, this paper comprehensively reviews the various aggregation technologies being used in distribution networks including the modeling strategy of air conditioning load aggregation, control strategy, control method, and application analysis. Moreover, future research directions are summarized as a guide to improve the technology of air conditioning load aggregation.